Lipids and Free Fatty Acids of Red Sea Avrainvillea amadelpha, Holothuria atra, and Sarcocornia fruticosa Inhibit Marine Bacterial Biofilms - Hawas, Usama W.; Shaher, Fekri; Ghandourah, Mohamed; Abou El-Kassem, Lamia T.; Satheesh, Sathianeson; Al-Sofyani, Abdul Mohsin A. (Letters in Organic Chemistry, 2020)
This study aimed at evaluating the antibiofilm activity of the Red Sea metabolites from green alga Avrainvillea amadelpha, sea cucumber Holothuria atra and costal plant Sarcocornia fruticosa against three biofilm bacterial strains isolated from Jeddah coast. Free fatty acids (FFAs) and other lipoidal matters were extracted from these organisms and analyzed by GC-MS. The composition of lipoidal fractions showed that A. amadelpha is rich by 74% saturated FAs, while sea cucumber H. atra revealed high content (60%) of unsaturated FAs. Palmitic acid is the major FA component in all species ranging from 14.5 to 26.7%. Phytol, sterols and hydrocarbons (C8-C29) were represented in the alga A. amadelpha as high contents with values 25.8, 21.9 and 18.5%, respectively. The extracts and lipoidal contents showed biofilm inhibitory activity against the isolated bacterial strains, where the unsaponified lipoidal fraction of S. fruticosa exhibited highest inhibitory activity against Planomicrobium sp. at concentration of 200 μg/mL.
Keywords: fatty acids